MADRASAH, PONDOK PESANTREN DAN REVOLUSI INDUSTRI 4.0 - Muhammad Ridho Sullam (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2020)
Madrasah and pondok pesantren as institution of islamic education a lot of using the coventional system. While this time, they are required to be ready confront the opportunities and challenge of industry era 4.0 in education. Therefore, needed efforts right and antisipative to minimize negative effects about institution of islamic education. This article are write to know efforts right done of madrasah and pondok pesantren in the address as well as harness the opportunities and challenge of industry era 4.0 by applying descriptive qualitative method and doing research to some references and literatures for researching data are needed. The result is the opportunities industry revolution 4.0 is the advances in technology that generates innovation that facilitate the learning process in the classroom and activities that took place in islamic educational institution, while the challenge is the rise of disruptive innovation who had managed to shift lifestyle and mindset of world people, like using e-book for replacing function of book. As for the deal is: 1) modifiy curriculum and learning according needs and technological developments; 2) increase in the ability and skill of students for competitive output; 3) strengthen the value of culture and the character of national anthem is integrated. These things are expected to keep the existance of madrasah and pondok pesantren in order to produce output competitive in the era of industry revolution 4.0.